STRUCTURAL AND FUNCTIONAL MONITORING OF EXTRAMACULAR CYSTOID SPACES IN A CASE OF X-LINKED RETINOSCHISIS TREATED WITH ACETAZOLAMIDE. Issue Volume 12:Issues 4(2018) (2018) - Collison, Frederick T.; Fishman, Gerald A.
Abstract : Background: Carbonic anhydrase inhibitors (CAIs) have been shown to have a beneficial effect on cystoid macular edema in X-linked retinoschisis (XLRS) and other inherited retinal conditions. The effect of CAIs outside the macula has been less well studied. Methods: Snellen visual acuity, spectral-domain optical coherence tomography (SD-OCT), kinetic visual field, and dark-adapted single-flash full-field electroretinogram (ERG) testing were all done at baseline and at least one follow-up visit. A 55-year-old male diagnosed with XLRS exhibited extensive macular and extramacular cystoid splitting in the right eye and was treated with oral extended-release acetazolamide 500 mg/day. Results: By 6 months of follow-up on acetazolamide treatment, SD-OCT demonstrated resolution of cystoid spaces both within the macula and out to the midperiphery. Visual acuity improved from 20/70 to 20/30. The full-field ERG was distinctly electronegative at both baseline and at a follow-up visit, with oscillatory potentials becoming more apparent at the follow-up visit. Peripheral visual field boundaries did not change significantly. Conclusion: This report demonstrates structural resolution of cystoid spaces throughout much of the retina in a patient with XLRS, adding to a published case report in which we first noted that extramacular cystoid spaces observed in XLRS may respond to CAI treatment. To our knowledge, this is the first reported study of follow-up functional studies (ERG and perimetry) in a CAI treatment responder with XLRS. Abstract : This report demonstrates structural resolution of both macular and extramacular cystoid spaces in an XLRS patient treated with oral acetazolamide. Although visual acuity improved, functional testing with full-field ERG and kinetic visual field was grossly unchanged with treatment.